Port–Shipping Interplay: A Multi-Stage Analysis of Facility Upgrades and Cargo Movement - Ming Wu; Xin Li; Yan Chen (Mathematics)
The ports and shipping industry is crucial in the global supply chain. Amid complex market and geopolitical dynamics, strengthening stakeholder collaboration becomes imperative to enhance maritime supply chain profit. Therefore, we develop a three-stage game model consisting of a port operator and a shipping company. We consider the impact of upgrading port facilities with advanced technology on the logistic decisions of the shipping company. In the first stage, the port decides whether to invest in upgrades, while the shipping company chooses one-way or two-way logistics. In subsequent stages, the port sets cargo handling charges, and the shipping company determines the freight rate. Equilibria under decentralized and centralized decision frameworks are derived. The equilibrium results show that market size has a significant effect on the shipping company’s choice. Specifically, the shipping company prefers two-way logistics when the market size is moderate, while one-way logistics is preferred when the market size is large or small. In addition, based on the fixed costs associated with port facility upgrades and two-way logistics, it is found that there exist three possible equilibria. Moreover, further analysis suggests that collaboration between the two parties, under appropriate financial conditions, can result in mutually beneficial outcomes. Our findings highlight the critical role of port–shipping company collaboration in enhancing operational efficiency and achieving greater mutual benefits.